Pragmatic Prediction in the Processing of Referring Expressions Containing Scalar Quantifiers - Macuch Silva, Vinicius; Franke, Michael (Frontiers in Psychology, 2021)
Previous research in cognitive science and psycholinguistics has shown that language users are able to predict upcoming linguistic input probabilistically, pre-activating material on the basis of cues emerging from different levels of linguistic abstraction, from phonology to semantics. Current evidence suggests that linguistic prediction also operates at the level of pragmatics, where processing is strongly constrained by context. To test a specific theory of contextually-constrained processing, termed pragmatic surprisal theory here, we used a self-paced reading task where participants were asked to view visual scenes and then read descriptions of those same scenes. Crucially, we manipulated whether the visual context biased readers into specific pragmatic expectations about how the description might unfold word by word. Contrary to the predictions of pragmatic surprisal theory, we found that participants took longer reading the main critical term in scenarios where they were biased by context and pragmatic constraints to expect a given word, as opposed to scenarios where there was no pragmatic expectation for any particular referent.